Ecological Restoration Focused on “Biodiversity Heritage Relicts” in Social-Ecological System: A Case Study Application - Semeraro, Teodoro (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Landscapes are the result of interactions, on a number of scales, between ecological processes, economic activities and the administrative and political organisation of society. Therefore, as a consequence of human transformations over time, some landscapes may contain residual degraded habitats hosting historical natural biodiversity that we may call "biodiversity heritage relicts". From this perspective, the aim of the paper is to describe an applicative approach to ecological restoration in social-ecological landscapes. The strategy involves employing GIS analysis along with field work and phytosociological techniques to restore vegetation. The process involves experts and stakeholders in order to strengthen the measures' resilience through time and consolidate the value of the landscape. The approach was applied in the municipality of Campi Salentina, Puglia region, Italy, and the result was the restoration of an important riparian habitat classified under Directive 92/43/EEC as “Salix alba and Populus alba galleries” (code 92A0), which had not previously been recorded in the Salento. In this case, the project re-established a natural habitat that represented a “biodiversity heritage relict” in the landscape, i.e. a community that had been present in the past but had become fragmented and partially destroyed by agricultural activity. The paper shows that the direct application of GIS analysis alone may not be sufficient to achieve ecological restoration in a social-ecological system on a local scale. The efficiency of ecological restoration efforts can be increased by using a phytosociological approach in conjunction with direct knowledge of the environment and the capacity to recognise "biodiversity heritage relicts." Integration of social and institutional elements into initiatives also contributes to the sustainability of the measures over time. Indeed, an ecological restoration project unfolding within a Socio-Ecological System requires institutions that value creativity and flexibility, viewing such projects as experiments for learning and acquiring new knowledge, and recognise the importance of participation as the key to successful measures.